Transport of natural soil nanoparticles in saturated porous media: effects of pH and ionic strength. Issue 1 (1st January 2017) - Jiang, Yanji; Yu, Lin; Sun, Huimin; Yin, Xianqiang; Wang, Changzhao; Mathews, Shiny; Wang, Nong
Abstract: To understand the effects of ionic strength and pH on the transport of natural soil nanoparticles (NS) in saturated porous media, aeolian sandy soil nanoparticles (AS), cultivated loessial soil nano particles (CS), manural loessial soil nanoparticles (MS) and red soil nanoparticles (RS) were leached with solutions of varying pH and ionic strength. The recovery rate of soil nanoparticles decreased in the order AS > RS > MS > CS. Transport of soil nanoparticles was enhanced with increasing pH and decreasing ionic strength and was attributable to changes in the Zeta potential of NS. Deposition of NS was also affected by the composition of soil nanoparticles and the surface charge. Column experiments showed that the interaction between soil nanoparticles and saturated quartz sand was mainly due to the physical and chemical properties of soil nanoparticles. The Derjaguin–Landau–Verwey–Overbeek interaction energies between NS and sand were affected by pHs and ionic strengths. Soil nanoparticles transport through saturated porous media could be accurately simulated by the one-dimensional advection-dispersion-reaction equation.